Moderate Treadmill Exercise Training Improves Cardiovascular and Nitrergic Response and Resistance to Trypanosoma cruzi Infection in Mice - Lucchetti, Bruno F. C.; Zanluqui, Nágela G.; de Ataides Raquel, Hiviny; Lovo-Martins, Maria I.; Tatakihara, Vera L. H.; de Oliveira Belém, Mônica; Michelini, Lisete C.; de Almeida Araújo, Eduardo J.; Pinge-Filho, Phileno; Martins-Pinge, Marli C. (Frontiers in Physiology, 2017)
There is evidence suggesting that exercise training (ET) acts as a factor towards resistance to Trypanosoma cruzi infection. However, the effects of mean arterial pressure (MAP), heart rate (HR), and nitric oxide (NO) during the acute phase of infection has not been elucidated yet. Swiss mice were randomly assigned into four groups: sedentary control (SC, n=30), trained control (TC, n=30), sedentary infected (SI, n=30), and trained infected (TI, n=30). ET was performed on the treadmill for nine weeks. After training, the mice were infected with 5 × 103 trypomastigotes of T.cruzi (Y strain) or PBS. We observed resting bradycardia and improved performance in trained animals compared with sedentary ones. On the 20th day post-infection (DPI), we found a decrease in HR in SI animals compared to TI animals (699.73 ± 42.37 vs. 742.11 ± 25.35 bpm, respectively, P < 0.05). We also observed increased production of NO in cardiac tissue on the 20th DPI in the SI group, normalized in TI group (20.73 ± 2.74 vs. 6.51 ± 1.19 μM, respectively). Plasma pro-inflammatory cytokines (IL-12, TNF-α, IFN-,) and MCP-1 were increased in SI animals, but decreased in TI animals. The increase in parasitemia on the 15th and 17th DPI in the SI group was attenuated in the TI group. Our results suggest that previous ET plays a preventive role in resistance to T.cruzi infection, modulating cardiovascular aspects, inflammatory reaction, and NO levels of infected mice.